Peran Digital Marketing Berbasis Artificial Intelligence dalam Meningkatkan Customer Engagement dan Conversion Rate - Hilman Kusnadi; Lutfi Hidayat; Fauzan Naufal (Program Studi Ekonomi Islam Fakultas Ekonomi Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2025)
This study aims to analyze the role of Artificial Intelligence (AI)-based digital marketing in increasing customer engagement and conversion rates. The development of digital technology has driven significant changes in marketing strategies, with AI becoming a key element in optimizing the interaction and effectiveness of marketing campaigns. This study uses a quantitative approach with an explanatory research design to examine the causal relationship between AI-based digital marketing as the independent variable, customer engagement as the mediating variable, and conversion rate as the dependent variable. Data were collected through a Likert-scale questionnaire distributed to active users of digital platforms who have interacted with AI technology in marketing. Data analysis was performed using linear regression and Structural Equation Modeling (SEM) to examine the relationship between variables and the role of mediators. The results show that AI-based digital marketing has a positive and significant influence on customer engagement and conversion rates. Furthermore, customer engagement is proven to act as a mediating variable, strengthening the relationship between AI and conversion rates. These findings suggest that increased conversion is not only directly influenced by AI technology but also through higher consumer engagement. This study provides theoretical contributions to the development of AI-based marketing models and provides practical implications for companies in designing more effective, adaptive, and data-driven marketing strategies. Thus, the integration of AI in digital marketing is a key factor in improving marketing performance in the digital age.